An Evaluation of Ahmad Dahlan Impacting to The Leadership In Indonesia - Anton Sebastian; Stanley Stanley (Jurnal Didaskalia, 2019)
Ahmad Dahlan is the fourth child. Born in 1868 to a traditional Muslim family domiciled in Kauman, a religious village in Yogyakarta. The village is located just beside the Sultan Palace of Yogyakarta, and is a well-known village inhabited by Muslims. When he was a child, his name was Muhammad Darwisy. Upon returning from Mecca, he changed his name to Ahmad Dahlan. His father Kiai Haji Abu Bakar bin Haji Sulaiman, was the official Kotib of the Great Mosque of the Sultanate of Yogyakarta. His mother named Siti Aminah was the daughter of Religious Judge Kiai Haji Ibrahim. According to the biographers of Ahmad Dahlan, one of Dahlan's ancestors was the first and most famous guardian of Wali Songo, Maulana Malik Ibrahim. Even the Dutch report said he was Arabic. This report may be true because based on this genealogical background, which was strengthened by his interest in reform ideas, Ahmad Dahlan - before establishing his own organization - joined Jamiat Kheir and later sent his son to study at the school the organization had founded. This paper aims to see to what extent the approach strategy and values used by Ahmad Dahlan to advance Islamic teachings? What is the Government's attitude towards what Ahmad Dahlan has done? Then, how is the author's critical evaluation of Ahmad Dahlan's approach to strategy to education in Indonesia? Application: challenge Indonesian national educators.